2005
DOI: 10.1186/1471-213x-5-11
|View full text |Cite
|
Sign up to set email alerts
|

FGF10/FGFR2b signaling plays essential roles during in vivo embryonic submandibular salivary gland morphogenesis

Abstract: BackgroundAnalyses of Fgf10 and Fgfr2b mutant mice, as well as human studies, suggest that FGF10/FGFR2b signaling may play an essential, nonredundant role during embryonic SMG development. To address this question, we have analyzed the SMG phenotype in Fgf10 and Fgfr2b heterozygous and null mutant mice. In addition, although previous studies suggest that the FGF10/FGFR2b and FGF8/FGFR2c signaling pathways are functionally interrelated, little is known about the functional relationship between these two pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 38 publications
9
63
1
Order By: Relevance
“…In the present study, moderate immunoreactions for FGFR-1 were observed at the ICD of normal and Day 14, and slight immunoreactions were found in NFAC and MAC during regeneration. Previous studies have shown that FGFR-2 as the receptor of FGF-10 is very important in submandibular gland development (Celli et al 1998;Ohuchi et al 2000;Jaskoll et al 2005). However, our results showed that FGFR-2 was not expressed in the duct ligation model of submandibular gland regeneration.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In the present study, moderate immunoreactions for FGFR-1 were observed at the ICD of normal and Day 14, and slight immunoreactions were found in NFAC and MAC during regeneration. Previous studies have shown that FGFR-2 as the receptor of FGF-10 is very important in submandibular gland development (Celli et al 1998;Ohuchi et al 2000;Jaskoll et al 2005). However, our results showed that FGFR-2 was not expressed in the duct ligation model of submandibular gland regeneration.…”
Section: Discussioncontrasting
confidence: 81%
“…Out of these, fibroblast growth factors (FGFs) consisting 22 family members (Itoh and Ornitz 2004) play crucial roles. For example, FGF-8/FGF receptor (FGFR)-2(IIIc) (Jaskoll et al 2002) and FGF-10/FGFR-2(IIIb) (Ohuchi et al 2000;Jaskoll et al 2005) signals contribute to bud formation and branching of the embryonic submandibular gland. FGF-2 (Madan and Kramer 2005) and -7 (Guo et al 1993) play possibly roles in differentiation of the salivary gland.…”
Section: Introductionmentioning
confidence: 99%
“…However, expression of Fgf10 and FGFR2b targets, Etv4 and 5 , were unchanged (Figure 7C). In addition, reduction of FGF10/FGFR2b signaling ex vivo (Figure S6A (Steinberg et al, 2005)) or in vivo (Figure S6B; (Jaskoll et al, 2005)) had no effect on ductal development. Together, these data indicate that deficient VIP-dependent innervation results in impaired SMG tubulogenesis in vivo .…”
Section: Resultsmentioning
confidence: 98%
“…Nrg1-III deficient salivary glands were devoid of functional nerves and exhibited aberrant ductal morphogenesis: epithelial branching was reduced (Figure 7A and B) with disrupted lumen formation (Figure 7A, ZO1 immunostaining, lower panel) and expansion (Figure 7D and F, arrows). We next asked whether this phenotype was due to loss of FGF10/FGFR2b signaling, an essential regulator of epithelial branching in the SMG (Jaskoll et al, 2005). However, expression of Fgf10 and FGFR2b targets, Etv4 and 5 , were unchanged (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…This syndrome presents as aplasia and/or hypoplasia of the salivary and lacrimal glands, and also abnormalities of the ears, eyes, face, mouth, teeth, digits and genitourinary system. Again, mice with similar genetic mutations have similar defects in salivary gland biogenesis and have been used to study how FGF signaling affects gland biogenesis [24,25]. …”
Section: Salivary Gland Biogenesismentioning
confidence: 99%